A study on the early degradation of the non-additive polypropylene–polyethylene composite sampled between the polymerization reactor and the deactivation-degassing tank (2024)
The industrial production of polypropylene–polyethylene composites (C-PP-PE) involves the generation of waste that is not usable, resulting in a significant environmental impact globally. In this research, we identified different concentrations of aluminum (8–410 ppm), chlorine (13–205 ppm), and iron (4–100 ppm) residues originating from traces of the Ziegler–Natta catalyst and the triethylaluminum (TEAL) co-catalyst. These residues accelerate the generation of plastic waste and affect the thermo-kinetic performance of C-PP-PE, as well as the formation of volatile organic compounds that reduce the commercial viability of C-PP-PE. Several families of organic compounds were quantified by gas chromatography with mass spectrometry, and it is evident that these concentrations varied directly with the ppm of Al, Cl, and Fe present in C-PP-PE. This research used kinetic models of Coats–Redfern, Horowitz–Metzger, Flynn–Wall–Ozawa, and Kissinger–Akahira–Sunose. The activation energy values (Ea) were inversely correlated with Al, Cl, and Fe concentrations. In samples PP0 and W3, with low Al, Cl, and Fe concentrations, the values (Ea) were 286 and 224 kJ mol−1, respectively, using the Horowitz method. Samples W1 and W5, with a high ppm of these elements, showed Ea values of 80.83 and 102.99 kJ mol−1, respectively. This knowledge of the thermodynamic behavior and the elucidation of possible chemical reactions in the industrial production of C-PP-PE allowed us to search for a suitable remediation technique to give a new commercial life to C-PP-PE waste, thus supporting the management of plastic waste and improving the process—recycling to promote sustainability and industrial efficiency. One option was using the antioxidant additive Irgafos P-168 (IG-P168), which stabilized some of these C-PP-PE residues very well until thermal properties similar to those of pure C-PP-PE were obtained.